RedistribusiI Tanah Dalam Usaha Pengetasan Kemiskinan Masyarakat Petani:Simulasi Sistem Informasi Geografis dalam Kegiatan Redistribusi Tanah di Wilayah Provinsi Kalimantan Tengah - Cholid, Sofyan (UI Scholars Hub, 2006)
Nowadays the land use problem couldn’t be solved as we expected. However, it becomes more complicated in line to the increasing of various development and community activities. These activities require some efforts in managing human settlement in the case of land ownership. The very significant limitation and fundamental in executing settlement of authority and ownership of land is there’s no factual and actual data, either from object and subject land reform aspect. According to this study, poverty alleviation through land reform pattern is much assisted with exploiting a SIG technology because the analysis of capacities and ability the data in the amount is almost infinite. By overlap both thematic map types (object and subject potential), hence obtained the potency indication object-subject land reform in Kalimantan Tengah province in